2014
DOI: 10.1128/jcm.02572-13
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Sequence-Based Identification Scheme for Bordetella Reveals Several Putative Novel Species

Abstract: fThe differentiation of Bordetella species, particularly those causing human infection, is problematic. We found that sequence analysis of an internal fragment of nrdA allowed differentiation of the currently named Bordetella species. Analysis of 107 "Bordetella" isolates recovered almost exclusively from human respiratory tract specimens identified several putative novel species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 18 publications
(20 reference statements)
4
43
0
Order By: Relevance
“…Further studies reported isolation of B. hinzii -like organisms from a mouse that was imported from Australia to an animal research facility in Germany (Benga et al , 2014), from lungs of a mouse in the USA (Spilker et al , 2014) and from a mouse at an animal facility in Malaysia (Loong et al , 2016). In addition to laboratory mice, B.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies reported isolation of B. hinzii -like organisms from a mouse that was imported from Australia to an animal research facility in Germany (Benga et al , 2014), from lungs of a mouse in the USA (Spilker et al , 2014) and from a mouse at an animal facility in Malaysia (Loong et al , 2016). In addition to laboratory mice, B.…”
mentioning
confidence: 99%
“…nov. to other bordetellae, we extracted an internal fragment of the nrdA gene, which was previously shown to reliably differentiate named Bordetella species (Spilker et al , 2014), and we compared its sequence against the MLST database (pubmlst.org/bordetella/). All three B.…”
mentioning
confidence: 99%
“…Mice were inoculated intranasally with 10 6 B. pseudohinzii colony-forming units (CFUs), based on the culture and growth pattern of the bacteria. The strain of B pseudohinzii used was that originally isolated from our CF mouse colony [5,9]. Mice were followed daily and for up to 2 weeks, and weekly thereafter with weights and clinical score followed by plethysmography and bronchoalveolar lavage (BAL) at varying time points.…”
Section: Methodsmentioning
confidence: 99%
“…Next-generation sequencing technologies provide a less biased method of microbiota detection and identification by eliminating the need for culturing. With this approach, it is clear that microbial communities in the CF airways are diverse, including bacterial species such as Bordetella that were previously not typically associated with CF lung infections [5]. Bordetella infections can be particularly pathogenic because they are one of a few pathogens known to evade neutrophil extracellular traps, which are a key immune mechanism for respiratory infections [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation